Perception of health risk and compliance with preventive measures related to COVID-19 in the Czech population: preliminary results of a rapid questionnaire survey - Dalecká, Andrea; Šlachtová, Hana; Tomášková, Hana; Maďar, Rastislav (International journal of occupational medicine and environmental health, 2021)
OBJECTIVES: In the Czech Republic, an outbreak of the coronavirus disease (COVID‑19) has been decelerated by quickly adopting strict and strongly limiting government measures. In this study, the authors present the preliminary results (April 1-5, 2020) of a public risk perception study of COVID‑19. MATERIAL AND METHODS: The online questionnaire survey was announced in the national TV and radio stations with the nationwide coverage. Respondents were recruited through the website of the University of Ostrava during the first 5 days of the survey (N = 7966). The data covered risk perception with a focus on physical and psychological aspects, the current socio-economic situation and adaptation to the lockdown. The authors used Mann-Whitney and Kruskal-Wallis tests, as well as ordered logistic regression, with a significance level of 5% using STATA version 15. RESULTS: From the total sample of the respondents aged 40 years on average (a range of 15-87 years), the present study shows that women (p < 0.001) and elderly people (p < 0.001) perceived the health risk related to COVID‑19 as significantly worse than others. Older people (>60 years) perceived their mental health as significantly better than younger participants (p < 0.001). Most of the respondents assessed the adopted measures as adequate (71%) and believed in their effectiveness (69.7%). CONCLUSIONS: This study contributes to understanding the risk perception as a public response to the COVID‑19 pandemic. Int J Occup Med Environ Health. 2021;34(2):165-76.
Keywords: Surveys and Questionnaires; COVID‑19; pandemie; questionnaire survey; kontrola infekčních nemocí; Mental Health; Humans; Perception; lidé středního věku; Communicable Disease Control; duševní zdraví; Female; Aged; mladý dospělý; dospělí; Pandemics; senioři; lidé; risk communication; průzkumy a dotazníky; Adult; COVID-19; health risk perception; ženské pohlaví; percepce; Male; Middle Aged; Adolescent; Czech Republic; Aged, 80 and over; preventive measures; Young Adult; senioři nad 80 let; Česká republika; mužské pohlaví; SARS-CoV-2; mental health; mladiství